KRAS, NRAS, BRAF signatures, and MMR status in colorectal cancer patients in North China. Issue 9 (3rd March 2023) - Lian, Shen-Yi; Tan, Lu-Xin; Liu, Xin-Zhi; Yang, Lu-Jing; Li, Ning-Ning; Feng, Qing; Wang, Ping; Wang, Yue; Qiao, Dong-Bo; Zhou, Li-Xin; Sun, Ting-Ting; Wang, Lin; et al.
Abstract : We assessed the clinicopathological features and prognostic values of KRAS, NRAS, BRAF, and DNA mismatch repair status in colorectal cancer (CRC) to provide real-world data in developing countries. We enrolled 369 CRC patients and analyzed the correlation between RAS/BRAF mutation, mismatch repair status with clinicopathological features, and their prognostic roles. The mutation frequencies of KRAS, NRAS, and BRAF were 41.7%, 1.6%, and 3.8%, respectively. KRAS mutations and deficient mismatch repair (dMMR) status were associated with right-sided tumors, aggressive biological behaviors, and poor differentiation. BRAF (V600E) mutations are associated with well-differentiated and lymphovascular invasion. The dMMR status predominated in young and middle-aged patients and tumor node metastasis stage II patients. dMMR status predicted longer overall survival in all CRC patients. KRAS mutations indicated inferior overall survival in patients with CRC stage IV. Our study showed that KRAS mutations and dMMR status could be applied to CRC patients with different clinicopathological features.